Android balloon game for children - Pulipaka, Mohana Saketh (Kansas State University, 2015)
Android balloon game application is an android application which helps in improving the children’s vocabulary power. This application provides a graphical user interface with words as questions and balloons as the options. The end user will have to select a balloon in order to select an answer. There are three modules in this application which are game mode, new game and high scores. In the basic module questions like Alpha_bet are included. Also as an enhancement, the game is made interesting by giving the user three lives to clear the levels of the game. Three small balloons are included in the application which resemble the three lives and once an incorrect answer is selected, the green balloon will be replaced by a red balloon depicting an incorrect answer. Also the scores will be computed for every correct option that is selected by the user. The score is incremented by ten points for every correct answer. And for the high score section, the game would maintain the list of top players. High score section will consist of the user’s name, score, time and date for the gameplay. Apart from that a next button is included which helps the user to skip a word which the user finds it difficult to answer. A hint option is also provided in the game which pronounces the word helping the user to guess the word correctly.
Keywords: Android Balloon Game; Computer Science (0984)